Sodium electrode layered oxide and preparation method and application thereof
Through the composite coating method of aluminum hydroxide-assisted perovskite coating layer and interface gradient doping, the problem of poor cycle stability of O3 type positive electrode materials under high voltage is solved, and the stability and safety under high voltage are improved.
Patent Information
- Application Number
- CN202511187233.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-09-19
- Estimated Expiration
- 2045-08-25
AI Technical Summary
O3-type positive electrode materials have poor cycling stability at high voltages, and exhibit interlayer slip, irreversible phase transitions, and lattice redox reactions, leading to rapid attenuation of battery capacity.
A composite coating method combining aluminum hydroxide-assisted perovskite coating layer and interface gradient doping is adopted to synthesize the positive electrode material through a solid phase method, and sintered at 600-800°C to form a uniform composite coating layer to improve the stability of the material.
It significantly improves the cycle stability and safety performance of the positive electrode material at high voltage, reduces side reactions, and extends the service life of the battery.
Smart Images

Figure CN120664605A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a sodium-ion layered oxide, a preparation method thereof, and an application, in particular to a sodium-ion layered oxide coated with perovskite assisted by aluminum hydroxide. Background Art
[0002] Sodium ion batteries have a similar electrochemical mechanism to lithium ion batteries and are regarded as an important supplement to lithium ion battery technology due to their advantages of low cost, environmental friendliness, and high safety. Among many cathode materials, O3-type cathode materials (Na x TMO2, 2 / 3 < x ≤ 1) have become one of the cathode materials with commercialization prospects because of their simple synthesis process and high theoretical capacity. In order to further improve the energy density of sodium ion batteries, increasing the charging cut-off voltage (> 4.0V) is an effective method. However, the cycle stability of O3-type cathode materials at high voltages (> 4.0V) still faces major challenges. The main reasons include: 1. At high voltages and in a deep sodiation state, interlayer slippage will occur, exacerbating the generation of irreversible phase transitions; 2. Anion redox reactions will cause the release of lattice oxygen, increasing insecurity; 3. Volume changes cause uneven stress distribution inside the material, which in turn leads to microcracks, increasing the occurrence of side reactions, and ultimately causing rapid decay of the battery capacity.
[0003] Traditional modification strategies mainly include: anion / cation doping (enhancing the stability of the layered structure by inhibiting phase transitions), surface coating (improving interface stability and preventing electrolyte corrosion), and construction of multiphase structures (reducing irreversible phase transitions), etc. Therefore, how to improve the cycle stability of O3-type cathode materials at high voltages remains a huge challenge.
[0004] The present invention proposes a novel sodium-ion layered oxide, including a cathode material and a coating layer on the surface of the cathode material particles; the coating layer includes perovskite and sodium metaaluminate. The composite coating method of the present invention, in which aluminum hydroxide assists in coating sodium-ion layered oxides with perovskite, combines interface gradient doping and surface coating, and a composite cathode material that takes into account high energy density and long cycle life can enhance the cycle stability of sodium ion batteries at high voltages. Summary of the Invention
[0005] The purpose of the present invention is to provide a sodium-ion layered oxide, a preparation method thereof, and an application, aiming at the problems existing in the prior art.
[0006] Perovskite compounds have high ionic conductivity and are an ideal coating material. The traditional solid-state dry mixing coating process is simple, low-cost, and easy for large-scale production. However, it often has the problem of uneven coating, resulting in poor coating effect, especially the cycle performance at high voltages cannot be significantly improved. Therefore, in this invention, aluminum hydroxide is introduced for auxiliary coating. Under the combined action of aluminum hydroxide and perovskite compounds, a uniform composite coating layer is formed. Combining with interfacial gradient doping, the cycle stability of the cathode material at high voltages of 4.1 - 4.2V can be significantly improved.
[0007] The object of this invention can be achieved through the following solutions: This invention provides a sodium-based layered oxide, including a cathode material and a coating layer on the surface of the cathode material particles; the coating layer includes perovskite and sodium meta-aluminate.
[0008] The perovskite and sodium meta-aluminate in the coating layer are obtained by sintering a perovskite compound and aluminum hydroxide coated on the surface of the cathode material particles.
[0009] As an embodiment of this invention, the cathode material is an O3-type sodium-based layered oxide. The cathode material is Na x TMO2; where, 2 / 3 < x ≤ 1, and TM is a transition metal element including one or more of Ni, Fe, Mn, Cu, Ti, Co, Nb, Zn, Y, Zr, Mo.
[0010] The cathode material Na x TMO2 is obtained by calcining a layered oxide precursor and Na2CO3 after mixing. The dosages of the layered oxide precursor and Na2CO3 are set according to the composition ratio in Na x TMO2, where the mass of Na2CO3 is 2.5 - 3.5% in excess, preferably 3%.
[0011] The O3-type sodium-based layered oxide is preferably NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, synthesized by the solid-phase method (one-time sintering). Specifically, Ni 1 / 3 Fe[[ID=312 , one or more of CaZnTiO4, CaCoTiO4, CaFe2TiO6, and CaNiTiO4.
[0013] As one embodiment of the present invention, the particle size of the positive electrode material is 5-20 μm, preferably 10-15 μm, and the thickness of the coating layer on the surface of the positive electrode material particle is 2-10 nm, preferably 2-6 nm.
[0014] As an embodiment of the present invention, the mass ratio of the positive electrode material to the total material in the coating layer is 1:(0.01-0.11), preferably 1:(0.01-0.1), and more preferably 1:(0.03-0.04); The mass ratio of perovskite to sodium aluminate in the coating layer is 1:(0.1-2.2), preferably 1:(0.1-2), and more preferably 1:(0.4-0.75).
[0015] The present invention provides a method for preparing the sodium layered oxide, comprising the following steps: The positive electrode material, perovskite compound and aluminum hydroxide are mixed, sintered and cooled to obtain sodium electrode layered oxide.
[0016] In one embodiment of the present invention, the aluminum hydroxide is one or more of nano-aluminum hydroxide powder (particle size not exceeding 100 nm) and aluminum hydroxide sol. The calcination of the solid-solid mixture (positive electrode material and perovskite compound) typically results in an uneven coating material. The aluminum hydroxide of the present invention primarily functions to uniformly distribute the perovskite compound to the surface of the positive electrode material in its molten state, leveraging its low melting point and amphoteric properties. A portion of the aluminum hydroxide reacts with residual alkali on the surface to form sodium metaaluminate, which forms a coating layer with the perovskite compound. Therefore, the introduction of aluminum hydroxide, leveraging its excellent fluidity in its molten state, allows the perovskite coating material to uniformly distribute to the surface of the positive electrode material.
[0017] As one embodiment of the present invention, the mass ratio of the positive electrode material, the perovskite compound, and aluminum hydroxide is 100:(0.5-5):(0.5-5), preferably 100:(1.5-3):(1-2), and more preferably 100:(2-2.5):(1-1.5).
[0018] In one embodiment of the present invention, the positive electrode material, perovskite compound, and aluminum hydroxide are mixed using a solid-solid or solid-solution method without the use of a solvent. This method achieves uniform solid-solid or solid-solution mixing at a certain mass ratio, followed by calcination, resulting in a simple process. Furthermore, the use of solvent mixing (such as water) can easily release Na from the positive electrode material, leading to structural damage and capacity degradation. The resulting coating may be lumpy and uneven on the surface.
[0019] As an embodiment of the present invention, the mixing method is ball milling mixing, and the ball milling mixing is divided into two stages. The parameters of the first stage are: revolution 800-1100 rpm, rotation ratio 50-100%, and time 60-120s; the parameters of the second stage are: revolution 1100-1500 rpm, rotation ratio 50-100%, and time 60-120s.
[0020] As an embodiment of the present invention, the sintering temperature is 600-800° C., preferably 600-750° C., more preferably 650-750° C., and the sintering time is 6-10 h.
[0021] The present invention is calcined at 600-800 ° C. Under the action of kinetics and thermodynamics, since the ions of Ca and Na are close in radius, they can easily enter the Na layer, making the Na near the interface + / Ca 2+ Ion exchange, forming a gradient Ca 2+ Doping layer, Ca doping has a significant improvement on the stability of high voltage. Compared with traditional bulk doping, interface gradient doping significantly improves the stability and structural integrity of the material without sacrificing capacity and rate performance. 2+ It can act as a pillar to reduce the phase structure changes caused by high voltage, and also expand the distance between sodium layers, reducing Na + Migration energy barrier, making Na + The diffusion kinetics are significantly improved, enhancing rate performance.
[0022] Transition metal ions (TM) in perovskite compounds are also gradiently doped into the surface layer, forming TMO6 octahedra, which further stabilize the transition metal layer in the matrix material and slow its slip under high voltage and high sodium removal. Furthermore, the strong TM-O enhances the redox reversibility of the transition metal and effectively suppresses irreversible oxygen evolution. Ultimately, this improves the stability of the layered cathode material under high voltage.
[0023] In one embodiment of the present invention, sintering is performed under a protective gas atmosphere. The protective gas comprises one or more of oxygen and nitrogen, preferably oxygen. The protective gas is flowed during sintering. The flow of the protective gas maintains a high level of gas purity within the furnace, removes some impurities, and avoids the use of gases such as air containing moisture, which can increase residual alkali.
[0024] As one embodiment of the present invention, the gas flow rate is 20-50 L / min, preferably 20-40 L / min.
[0025] As one embodiment of the present invention, the coating layer of the resulting sodium-electrolyte layered oxide is a composite coating layer comprising perovskite and sodium metaaluminate. Direct coating with sodium metaaluminate can also reduce side reactions and improve stability, but this is only effective at a low voltage of 4.0V. If the voltage is increased, the internal volume of the material structure changes significantly, and sodium metaaluminate coating alone cannot improve the material's stability.
[0026] The present invention mainly realizes both coating and doping of the composite cathode material of perovskite compounds. Compared with direct bulk doping, interface gradient doping does not lose capacity and can improve the stability of the cathode material under high voltage (greater than 4.1V). However, perovskite compounds have a high melting point, usually above 1000℃, and a large particle size. When mixed with the cathode material in the solid phase, direct solid-solid mixing, and calcination at 600-700℃, they usually cannot evenly cover the surface of the cathode material, hindering its performance. When sintered above 700℃, the cathode material particles (Na x The TMO2 (primary sintered particles) will re-melt, causing the particles to grow larger and become compacted, ultimately reducing capacity. Furthermore, the secondary sintering temperature is too high, increasing material sintering costs. Therefore, the introduction of low-melting-point aluminum hydroxide powder (melting point 300°C) evenly distributes the coating material to the surface of the cathode material while molten. It then reacts with residual alkali on the surface to form a fast ion conductor, sodium metaaluminate, which further forms a composite coating layer with the perovskite compound.
[0027] The present invention also provides a positive electrode plate, characterized in that it comprises the sodium layered oxide.
[0028] The present invention also provides a battery, characterized in that it comprises the positive electrode sheet.
[0029] The present invention also provides an application of a sodium-ion layered oxide in the preparation of a sodium-ion battery.
[0030] Compared with the prior art, the present invention has the following beneficial effects: (1) Aluminum hydroxide is amphoteric and has a low melting point (300°C). During the sintering process, it is in a molten state as a whole. At the same time, part of the aluminum hydroxide decomposes into aluminum oxide, which can react with the residual alkali (Na2CO3, NaOH) on the surface to reduce the residual alkali on the surface. The specific reaction formula is as follows: Al(OH)3+NaOH→NaAlO2+2H2O; 2Al(OH)3→Al2O3+3H2O; Al2O3+Na2CO3→2NaAlO2+CO2; (2) Low melting point and good fluidity in the molten state. Aluminum hydroxide can drive the perovskite coating material to evenly reach the surface of the positive electrode material to form a uniform coating layer; (3) After sintering at high temperature of 600-800℃, a composite coating layer of sodium aluminate and perovskite is formed, as well as Ca 2+ Interface gradient doping effectively reduces the interface side reactions between the positive electrode material surface and the electrolyte and slows down the volume change, thereby improving the cycle stability and safety performance under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, objects and advantages of the present invention will become more apparent upon reading the detailed description of non-limiting embodiments with reference to the following drawings: Figure 1 This is a SEM image of the positive electrode material obtained in Example 1 of the present invention; Figure 2 TEM image of the positive electrode material obtained in Example 1 of the present invention; Figure 3 This is a TEM image of the positive electrode material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The present invention is described in detail below with reference to specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, provide detailed implementation methods and specific operating procedures, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and a number of adjustments and improvements made under the premise of the concept of the present invention all fall within the protection scope of the present invention.
[0033] Example 1 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0034] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12) 2 g, nano aluminum hydroxide powder 1 g (the particle size of the nano aluminum hydroxide powder used in the example is 20 nm), after ball milling to mix evenly, sintered at 650 ° C for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain a coated positive electrode material (average particle size 11.6 μm, thickness of the coating layer is about 3.0 nm, the mass ratio of the total substance in the positive electrode material and the coating layer is 1:0.0302, and the mass ratio of perovskite to sodium aluminate in the coating layer is 1:0.526).
[0035] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0036] Example 2 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 0.5 Mn 0.5 O2 Materials: Ni 0.5 Mn 0.5 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 0.5 Mn 0.5 O2.
[0037] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12 ) 2g, nano-aluminum hydroxide powder 1g, after ball milling and mixing evenly, sintered at 650 ℃ for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain the coated positive electrode material (average particle size 11.3μm, thickness of the coating layer is about 3.1nm, the mass ratio of the total substance in the positive electrode material and the coating layer is 1:0.0301, and the mass ratio of perovskite to sodium aluminate in the coating layer is 1:0.527).
[0038] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0039] Example 3 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0040] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:1:2, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12 ) 1 g, and nano-aluminum hydroxide powder 2 g, were ball-milled and mixed evenly, and then sintered at 650 ° C for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain a coated positive electrode material (average particle size 11.0 μm, thickness of the coating layer is about 2.9 nm, the mass ratio of the total substance in the positive electrode material and the coating layer is 1:0.0219, and the mass ratio of perovskite to sodium aluminate in the coating layer is 1:2.181).
[0041] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0042] Example 4 This embodiment provides a sodium-electrolyte layered oxide assisted by aluminum hydroxide and coated with a perovskite, and the preparation method includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0043] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2.5:1.5, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12) 2.5 g, and 1.5 g of nano-aluminum hydroxide powder were ball-milled and mixed evenly, and then sintered at 650 ° C for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain a coated positive electrode material (average particle size 11.2 μm, thickness of the coating layer is about 4.1 nm, the mass ratio of the total substance in the positive electrode material and the coating layer is 1:0.0398, and the mass ratio of perovskite and sodium aluminate in the coating layer is 1:0.636).
[0044] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0045] Example 5 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0046] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:5:5, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12 ) 5g, nano-aluminum hydroxide powder 5g, after ball milling and mixing evenly, sintered at 650 ℃ for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain the coated positive electrode material (average particle size 11.5 μm, thickness of the coating layer is about 4.9 nm, the mass ratio of the total material in the positive electrode material and the coating layer is 1:0.1025, and the mass ratio of perovskite to sodium aluminate in the coating layer is 1:1.060).
[0047] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0048] Example 6 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0049] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material, 2g of perovskite compound (CaTiO3), and 1g of nano-aluminum hydroxide powder were ball-milled and mixed evenly. Then, the mixture was sintered at 650℃ for 6h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain the coated positive electrode material (average particle size 11.5 μm, thickness of the coating layer about 3.1 nm, mass ratio of total substance in positive electrode material and coating layer 1:0.303, mass ratio of perovskite and sodium aluminate in the coating layer 1:0.524).
[0050] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0051] Example 7 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0052] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material, 2g of perovskite compound (CaMgTiO4), and 1g of nano-aluminum hydroxide powder were ball-milled and mixed evenly, and then sintered at 650℃ for 6h in oxygen (maintaining the gas flow rate at 30 L / min). After natural cooling, the coated positive electrode material (average particle size 11.1 μm, thickness of the coating layer about 3.0 nm, mass ratio of total substance in positive electrode material and coating layer 1:0.0302, mass ratio of perovskite and sodium aluminate in the coating layer 1:0.527) was obtained.
[0053] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0054] Example 8 This embodiment provides a sodium-electrolyte layered oxide assisted by aluminum hydroxide and coated with a perovskite, and the preparation method includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0055] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12 ) 2 g and 1 g of nano-aluminum hydroxide powder were ball-milled and mixed evenly, then sintered at 750 °C for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain a coated positive electrode material (average particle size 11.5 μm, thickness of the coating layer about 3.3 nm, mass ratio of the total substance in the positive electrode material and the coating layer was 1:0.0300, and the mass ratio of perovskite to sodium aluminate in the coating layer was 1:0.528).
[0056] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0057] Example 9 This embodiment provides a sodium layered oxide, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0058] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12 ) 2 g and 1 g of nano-aluminum hydroxide powder were ball-milled and mixed evenly, then sintered at 800 °C for 6 h in oxygen (maintaining the gas flow rate at 30 L / min), and naturally cooled to obtain a coated positive electrode material (average particle size 11.3 μm, thickness of the coating layer about 3.2 nm, mass ratio of the total substance in the positive electrode material and the coating layer was 1:0.0301, and the mass ratio of perovskite to sodium aluminate in the coating layer was 1:0.524).
[0059] The ball milling parameters were as follows: the first stage revolution was 1000 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 1200 rpm, the rotation ratio was 70%, and the time was 120 s.
[0060] Example 10 This embodiment provides a sodium layered oxide coated with aluminum hydroxide sol-assisted perovskite, the preparation method of which includes the following steps: (1) Synthesis of NaNi by solid phase method 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 Materials: Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and Na2CO3 (3% excess by mass) were mixed evenly by ball milling, calcined at 900℃ for 12h in air atmosphere, and cooled naturally to room temperature to obtain the cathode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0061] (2) Preparation of coated positive electrode materials: According to the mass ratio of 100:2:1, 100g of positive electrode material and perovskite compound (CaCu3Ti4O 12 ) and 2 g of aluminum hydroxide sol (50% solids content) were placed in a ball mill and milled at high speed. The mixture was sintered at 650°C for 6 hours in an oxygen atmosphere (maintaining an airflow of 30 L / min). The resulting coated cathode material (average particle size 11.4 μm, coating thickness approximately 2.9 nm, total mass ratio of cathode material to coating layer 1:0.0300, and mass ratio of perovskite to sodium metaaluminate in the coating layer 1:0.515) was obtained.
[0062] The ball milling parameters were as follows: the first stage revolution was 1500 rpm, the rotation ratio was 70%, and the time was 120 s; the second stage revolution was 2000 rpm, the rotation ratio was 70%, and the time was 120 s.
[0063] Comparative Example 1 This comparative example provides a sodium layered oxide, and the preparation method is basically the same as that of Example 1, except that: in step (2), no nano aluminum hydroxide powder or perovskite compound is added for coating.
[0064] Comparative Example 2 This comparative example provides a sodium layered oxide, and the preparation method is basically the same as that of Example 1, except that: in step (2), no nano-aluminum hydroxide powder is added for coating.
[0065] Comparative Example 3 This comparative example provides a sodium layered oxide, and the preparation method is basically the same as that of Example 1, except that in step (2), the nano-aluminum hydroxide powder is replaced with an equal mass of aluminum oxide powder.
[0066] Alumina powder has a high melting point (greater than 2000℃) and cannot be melted when calcined at 600-700℃, resulting in a uniform coating effect.
[0067] Comparative Example 4 This comparative example provides a sodium layered oxide, and the preparation method is basically the same as that of Example 1, except that in step (2), the nano-aluminum hydroxide powder is replaced with an equal mass of sodium metaaluminate.
[0068] Performance testing: 1. Residual alkali content detection: acid-base titration test 1) The test method for residual alkali (sodium carbonate) content in the sample is: Weigh the sample into a beaker, record the sample mass (y1 g), add (V1 ml) of ethylene glycol using a pipette, seal the beaker with plastic wrap, and stir for at least 10 minutes. After stirring, filter using a funnel. Take (V2 ml) of the resulting filtrate and stir and mix with 4 times (V2 ml) of pure water to obtain a mixed solution. Add 2-4 drops of methyl red-bromocresol green indicator solution to the mixed solution. Then, titrate with a standard hydrochloric acid solution with a concentration of c mol / L until the solution turns from green to slightly pink. Record the amount of hydrochloric acid consumed at this time (V3). Calculate the residual alkali (sodium carbonate) content of the sample according to the following formula:
[0069] 2) The test method for residual alkali (sodium hydroxide) content in the sample is: Weigh the sample into a beaker, record the sample mass (y2 g), add (V4 ml) of ethanol using a pipette, seal the beaker with plastic wrap, and stir for at least 10 minutes. After stirring, filter using a funnel, take (V2 ml) of the resulting filtrate, and stir and mix with 4 times (V2 ml) of pure water to obtain a mixed solution. Add 2 to 4 drops of methyl red-bromocresol green to the mixed solution. Then titrate with a cmol / L standard hydrochloric acid solution until the solution changes from green to slightly pink. Record the amount of hydrochloric acid consumed (V5) at this point. Calculate the residual alkali (sodium hydroxide) content of the sample according to the following formula:
[0070] 3) Calculate the total residual alkali content of the sample based on the test results of steps 1) and 2) of the above method. The formula is as follows:
[0071] 2. Electrochemical performance test: Button cells (assembled using the same method as the 2032 model) were charged and discharged at 25±2°C over a voltage range of 2.0-4.2V. The test values were as follows: initial discharge capacity at a 0.1C rate, initial discharge capacity at a 1C rate, and capacity retention after 50 cycles at a 1C rate. Rate performance was calculated as: initial discharge capacity at 1C / initial discharge capacity at 0.1C.
[0072] The button battery is composed of a positive electrode shell, a spring sheet, a gasket, a positive electrode plate, a separator, a negative electrode plate, and a negative electrode shell. The positive electrode plate is made of the prepared positive electrode material, the separator is a glass fiber separator, and the negative electrode is a metal sodium plate.
[0073] The positive electrode material pole piece was prepared as follows: the positive electrode slurry was prepared by mixing the positive electrode powder, PVDF, and conductive carbon black in N-methylpyrrolidone in a mass ratio of (92:4:4), coating, drying, and cutting to obtain a disc with a diameter of 15 mm.
[0074] The coin cell assembly procedure is to place the positive electrode casing flat on an insulating surface, clamp the positive electrode sheet and place it in the center of the casing. Add an appropriate amount of electrolyte (1.0M NaPF6 in EC:DMC = 1:1 vol%), then add the separator, negative electrode sheet, gasket, spring sheet, and negative electrode casing in that order. The battery is then sealed in a sealing machine to produce a button cell. The entire process is performed in an argon glove box. Performance test results are shown in Table 1.
[0075] Table 1 Performance test of batteries assembled from sodium layered oxides obtained in Examples and Comparative Examples
[0076] The particle size and coating thickness of the sodium layered oxides of each example were measured using scanning electron microscopy and transmission electron microscopy. The specific contents of Ca and Al in the coating layer were determined by ICP analysis, and the masses of the perovskite and sodium metaaluminate were then derived, as shown in Table 2 below.
[0077] Table 2 Particle size, coating thickness and composition of sodium layered oxide obtained in Example
[0078] Table 2 shows that the average particle size of the coated examples is 11-12 μm, the coating layer thickness is 3-5 nm, and the amount of material in the coating layer is close to the amount added.
[0079] like Figure 1 The following is a scanning electron microscope image of Example 1. It can be seen from the figure that the average particle size of the synthesized layered oxide positive electrode material is 11.6 μm. As can be seen from Table 1, when Example 1 is compared with Comparative Example 1, it is found that 2% CaCu3Ti4O 12 After coating with 1% Al(OH)3, the 0.1C initial discharge capacity did not significantly decrease, and the residual alkali content after secondary calcination was reduced to 3261 ppm. At a high voltage of 4.2V, its rate capability and 50-cycle retention rate were 90.6% and 91.2%, respectively, higher than the 86.4% and 67.5% of the uncoated comparative example 1, demonstrating excellent stability at high voltages. Figure 2 and Figure 3 They are transmission electron microscope scanning images of Example 1 and Comparative Example 2 respectively. Figure 2 As shown in FIG, a uniform composite coating layer with a thickness of 3 nm can be seen on the surface of the positive electrode material. Figure 3 shown) only CaCu3Ti4O 12 The coating layer is obviously uneven, indicating that the addition of 1% Al(OH)3 can improve the CaCu3Ti4O 12The coating layer is evenly distributed and forms a composite coating layer, which can effectively reduce the interface side reactions between the surface of the positive electrode material and the electrolyte and slow down the volume change, thereby improving the cycle stability and safety performance under high voltage.
[0080] Example 2 is NaNi 0.5 Mn 0.5 O2 cathode material coated with 2% CaCu3Ti4O under the same conditions 12 +1% Al(OH)3, 4.2V voltage, 50 cycles at 1C rate showed a cycle retention rate of 90.6%. This indicates that this coating condition is also applicable to other cathode materials and can achieve good stability at high voltages.
[0081] Compared with Example 1, Example 3 changes the CaCu3Ti4O 12 The mixing ratio of CaCu3Ti4O is 1:2. The first discharge capacity at 0.1C does not decrease significantly. The cycle retention rate at 1C is only 83.4%, which is lower than 91.2% of Example 1. 12 When the content is low, the interface gradient doping of Ca on the surface of the material is low, and its role in stabilizing the structure is limited.
[0082] Example 4 and Example 5 respectively increase the coating amount to 2.5% CaCu3Ti4O 12 +1.5%Al(OH)3 and 5%CaCu3Ti4O 12 +5%Al(OH)3, compared with Example 1, has the effect of reducing residual alkali. However, the 0.1C first discharge capacity of Example 4 and Example 5 is 182.4 mAh / g and 176.1 mAh / g, which is significantly lower than that of Example 1. Moreover, with the increase of coating amount, the rate performance is also poor, only 87.4% and 80.3%. This is mainly because the coating layer is too thick, which hinders the Na + The embedding and extraction of the coating lead to a significant decrease in electrochemical performance. Therefore, the coating amount also needs to be within an appropriate range.
[0083] Examples 6 and 7, using CaTiO3, CaMgTiO4, and Al(OH)3 as composite coatings, respectively, also demonstrated excellent cycling stability. At 4.2 V, the capacity retention rates after 50 cycles at 1C were 91% and 90.8%, respectively, similar to those in Example 1. This demonstrates that nano-aluminum hydroxide powder is also suitable for assisting the uniform coating of other perovskite compounds.
[0084] Examples 8 and 9 show that if the secondary sintering temperature is too high, exceeding 750°C, the particles will remelt and become agglomerated, resulting in a decrease in the 0.1C first charge capacity and worse cycle performance. Therefore, secondary sintering and coating need to be performed at an appropriate temperature.
[0085] Example 10, using aluminum hydroxide sol to assist perovskite coating, also demonstrated excellent cycling stability. At 4.2V, the initial discharge capacity at 0.1C was 186.8 mAh / g, and the 1C 50-cycle retention rate was 90.9%, similar to that of Example 1. This demonstrates that coating with aluminum hydroxide sol can achieve the same effect as coating with nano-aluminum hydroxide powder.
[0086] Comparative Example 2 is compared with Example 1, only 2% CaCu3Ti4O is coated 12 Although it can improve the rate capability and cycle stability, the coating is uneven, resulting in increased side reactions with the electrolyte. The 50-cycle cycle retention rate at 4.2V is 80.4%, which is lower than the 91.2% in Example 1.
[0087] Compared with Example 1, the 0.1C first discharge capacity of Comparative Example 3 is 184.8 mAh / g, which is lower than 187.1 mAh / g of Example 1, and the rate performance also decreases to 87.1%, which is lower than 90.6% of Example 1. Since alumina is an inert compound, the first capacity and rate performance will decrease after coating. In addition, Al2O3 has a high melting point of 2050°C and does not play an auxiliary role in the coating of perovskite. During the second calcination, it cannot melt and drive the perovskite to reach the surface of the material evenly. Therefore, the 1C, 50-cycle cycle retention rate is only 82.8%, which is lower than 91.2% of Example 1.
[0088] Comparative Example 4 is 2% CaCu3Ti4O 12 After adding 1% NaAlO2 as a composite coating, the residual alkali was also reduced after coating compared with Comparative Example 1. The initial discharge capacity at 0.1C was 185.1 mAh / g, slightly lower than that of Example 1. Moreover, the 50-cycle retention rate at 1C rate was only 84.3%, lower than the 91.2% in Example 1. This indicates that the direct addition of NaAlO2 did not play a role in assisting the coating.
[0089] Therefore, under the optimal conditions, 1% Al(OH)3 assisted 2% CaCu3Ti4O 12 Coating, forming a uniform composite coating layer on the surface of the sodium-based layered positive electrode material, combined with interface gradient doping, can significantly improve its cycle stability at a high voltage of 4.2V.
[0090] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various variations or modifications within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A sodium layered oxide, characterized in that It includes a positive electrode material and a coating layer on the surface of the positive electrode material particles; the coating layer includes perovskite and sodium metaaluminate; The mass ratio of perovskite to sodium aluminate in the coating layer is 1:(0.1-2.2); The perovskite and sodium aluminate in the coating layer are obtained by sintering perovskite compounds and aluminum hydroxide mixed with positive electrode material particles.
2. The sodium layered oxide according to claim 1, characterized in that The positive electrode material is an O3-type sodium-ion layered oxide; the O3-type sodium-ion layered oxide is Na x TMO2; where 2 / 3 < x ≤ 1, and TM is a transition metal element including one or more of Ni, Fe, Mn, Cu, Ti, Co, Nb, Zn, Y, Zr, and Mo.
3. The sodium layered oxide according to claim 1, characterized in that The perovskite compound is CaABO x ; Wherein AB includes one or more of Ti, Mg, Co, Fe, Ni, Cu, and Zn.
4. The sodium layered oxide according to claim 1, characterized in that The average particle size of the positive electrode material is 5-20 μm; and / or, the coating layer on the surface of the positive electrode material particles has a thickness of 2-10 nm; And / or, the mass ratio of the positive electrode material to the total substance in the coating layer is 1:(0.01-0.11).
5. A method for preparing a sodium layered oxide according to any one of claims 1 to 4, characterized in that: The steps include: The positive electrode material, the perovskite compound and the aluminum hydroxide are mixed, sintered and then cooled to obtain the sodium electrode layered oxide.
6. The method for preparing the sodium layered oxide according to claim 5, wherein: Aluminum hydroxide is one or more of nano aluminum hydroxide powder and aluminum hydroxide sol; and / or, the mass ratio of the positive electrode material, the perovskite compound, and the aluminum hydroxide is 100:(0.5-5):(0.5-5); And / or, the sintering temperature is 600-800° C. and the sintering time is 6-10 hours.
7. The method for preparing sodium layered oxide according to claim 5, wherein: Sintering is carried out under the condition of protective gas; the protective gas includes one or more of oxygen and nitrogen.
8. A positive electrode plate, characterized in that: The invention comprises the sodium layered oxide according to any one of claims 1 to 4.
9. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 8.
10. Use of the sodium layered oxide according to claim 1 in preparing sodium ion batteries.
Citation Information
Patent Citations
Preparation method of aluminum oxide-coated positive electrode material for lithium-ion battery
CN106784837A
Sodium ion battery positive electrode material as well as preparation method and application thereof
CN112928252A
Sodium-ion battery positive electrode material and preparation method thereof, sodium-ion battery and power-related equipment
CN119601630A
Sodium metaaluminate coated sodium ion layered oxide positive electrode material, preparation method and application
CN120413630A
Multi-element positive electrode material and preparation method therefor, and lithium-ion battery
WO2024000155A1
Cited By
Modified positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN121460538A
Preparation method of sodium electrode layered oxide positive electrode material
CN121583888A